A geological cross section of Neogene to Quaternary sediments in the Larsemann Hills, East Antarctica - Nikita Demidov; Sergey Verkulich; Zinaida Pushina; Elizaveta Rivkina; Denis Shmelev; Oksana Zanina; Natalya Belova; Martin Melles; Janet Rethemeyer (Polar Science, 2025)

Soil development, mineralogy and organic matter stocks in a West Greenlandic tundra landscape - Tino Peplau; Patrick Liebmann; Claudia Fiencke; Selina Undeutsch; Christian Knoblauch; Stefan Dultz; Amira Hildebrandt; Lars Kutzbach; Bo Elberling; Laura Sophie Schnee; Jan Olaf Melchert; Janet Rethemeyer; et al. (CATENA, 2025)

Evaluating the isotopic composition of leaf organic compounds in fog-dependent Tillandsia landbeckii across the coastal Atacama Desert: Implications for hydroclimate reconstructions at the dry limit - Andrea Jaeschke; Christoph Böhm; Jan H. Schween; Enno Schefuß; Marcus A. Koch; Claudio Latorre; Sergio Contreras; Janet Rethemeyer; Holger Wissel; Andreas Lücke (Global and Planetary Change, 2024)

Microbial hotspots in a relict fog-dependent Tillandsia landbeckii dune from the coastal Atacama Desert - Andrea Jaeschke; S. Matthias May; Anna Hakobyan; Ramona Mörchen; Olaf Bubenzer; Stefano M. Bernasconi; Enno Schefuß; Dirk Hoffmeister; Claudio Latorre; Martina Gwozdz; Janet Rethemeyer; Claudia Knief (Global and Planetary Change, 2024)

Late Pleistocene to modern precipitation changes at the Paranal clay pan, central Atacama Desert - Volker Wennrich; Christoph Böhm; Dominik Brill; Rafael Carballeira; Dirk Hoffmeister; Andrea Jaeschke; Florian Kerber; Antonio Maldonado; Simon Matthias May; Lester Olivares; Stephan Opitz; Janet Rethemeyer; et al. (Global and Planetary Change, 2024)

Rewetting the hyper-arid Atacama Desert soil reactivates a carbon-starved microbial decomposer community and also triggers archaeal metabolism - Christoph Rosinger; Johannes Rousk; Michael Bonkowski; Janet Rethemeyer; Andrea Jaeschke (Science of The Total Environment, 2023)

Microbial methane cycling in sediments of Arctic thermokarst lagoons - Sizhong Yang; Sara E. Anthony; Maren Jenrich; Michiel H. in ’t Zandt; Jens Strauss; Pier Paul Overduin; Guido Grosse; Michael Angelopoulos; Boris K. Biskaborn; Mikhail N. Grigoriev; Dirk Wagner; Christian Knoblauch; et al. (Global Change Biology, 2023)
Thermokarst lagoons represent the transition state from a freshwater lacustrine to a marine environment, and receive little attention regarding their role for greenhouse gas production and release in Arctic permafrost landscapes. We studied the fate of methane (CH 4 ) in sediments of a thermokarst lagoon in comparison to two thermokarst lakes on the Bykovsky Peninsula in northeastern Siberia through the analysis of sediment CH 4 concentrations and isotopic signature, methane‐cycling microbial taxa, sediment geochemistry, lipid biomarkers, and network analysis. We assessed how differences in geochemistry between thermokarst lakes and thermokarst lagoons, caused by the infiltration of sulfate‐rich marine water, altered the microbial methane‐cycling community. Anaerobic sulfate‐reducing ANME‐2a/2b methanotrophs dominated the sulfate‐rich sediments of the lagoon despite its known seasonal alternation between brackish and freshwater inflow and low sulfate concentrations compared to the usual marine ANME habitat. Non‐competitive methylotrophic methanogens dominated the methanogenic community of the lakes and the lagoon, independent of differences in porewater chemistry and depth. This potentially contributed to the high CH 4 concentrations observed in all sulfate‐poor sediments. CH 4 concentrations in the freshwater‐influenced sediments averaged 1.34 ± 0.98 μmol g −1 , with highly depleted δ 13 C‐CH 4 values ranging from −89‰ to −70‰. In contrast, the sulfate‐affected upper 300 cm of the lagoon exhibited low average CH 4 concentrations of 0.011 ± 0.005 μmol g −1 with comparatively enriched δ 13 C‐CH 4 values of −54‰ to −37‰ pointing to substantial methane oxidation. Our study shows that lagoon formation specifically supports methane oxidizers and methane oxidation through changes in pore water chemistry, especially sulfate, while methanogens are similar to lake conditions.

Coupled Oceanic and Atmospheric Controls of Deglacial Southeastern South America Precipitation and Western South Atlantic Productivity - Karl J. F. Meier; Andrea Jaeschke; Janet Rethemeyer; Cristiano M. Chiessi; Ana Luiza S. Albuquerque; Vincent Wall; Oliver Friedrich; André Bahr (Frontiers in Marine Science, 2022)
Various mechanisms were proposed as substantial drivers of (sub)tropical South American hydroclimate changes during the last deglaciation. However, the interpretation of past precipitation records from the regions affected by the South American Summer Monsoon, the dominant hydroclimatic system in (sub)tropical South America, still insufficiently consider feedbacks between oceanic and atmospheric processes evident in modern observational data. Here, we evaluate ocean-atmosphere feedbacks active in the region from 19 to 4 ka based on a multi-proxy record comprising lipid biomarker, bulk sediment elemental composition and foraminiferal geochemistry from a sediment core retrieved from the tropical western South Atlantic offshore eastern Brazil at ~22°S. Our proxy data together with existing paleoclimate records show that the consideration of large scale synoptic climatic features across South America is crucial for understanding the past spatio-temporal rainfall variability, especially during the last deglaciation. While the paleohydrological data from our study site show relatively stable precipitation across the deglaciation in the core region of the South Atlantic Convergence Zone, distinct hydroclimatic gradients developed across the continent during Heinrich Stadial 1, which climaxed at ~16 ka. By then, the prevalent atmospheric and oceanic configuration caused more frequent extreme climatic events associated with positive rainfall in the northern portion of eastern South America and in the southeastern portion of the continent. These climatic extremes resulted from substantial warming of the sub(tropical) western South Atlantic sea surface that fostered oceanic moisture transport towards the continent and the reconfiguration of quasi-stationary atmospheric patterns. We further find that enhanced continental precipitation in combination with low glacial sea level strongly impacted marine ecosystems via enhanced terrigenous organic matter input in line with augmented nutrient release to the ocean. Extreme rainfall events similar to those that occurred during Heinrich Stadial 1 are likely to recur in South America as a consequence of global warming, because the projected reduction of the intra-hemispheric temperature gradient may lead to the development of atmospheric patterns similar to those in force during Heinrich Stadial 1.

Leaf wax composition and distribution of Tillandsia landbeckii reflects moisture gradient across the hyperarid Atacama Desert - Sergio Contreras; Manlio Landahur; Karla García; Claudio Latorre; Mark Reyers; Janet Rethemeyer; Andrea Jaeschke (Plant Systematics and Evolution, 2022)
In the hyperarid Atacama Desert, water availability plays a crucial role in allowing plant survival. Along with scant rainfall, marine advective fog frequently occurs along the coastal escarpment fueling isolated mono-specific patches of Tillandsia vegetation. In this study, we investigate the lipid biomarker composition of the bromeliad Tillandsia landbeckii (CAM plant) to assess structural adaptations at the molecular level as a response to extremely arid conditions. We analyzed long-chain n -alkanes and fatty acids in living specimens ( n = 59) collected from the main Tillandsia dune ecosystems across a 350 km coastal transect. We found that the leaf wax composition was dominated by n -alkanes with concentrations (total average 160.8 ± 91.4 µg/g) up to three times higher than fatty acids (66.7 ± 40.7 µg/g), likely as an adaptation to the hyperarid environment. Significant differences were found in leaf wax distribution (Average Chain Length [ACL] and Carbon Preference Index [CPI]) in the northern zone relative to the central and southern zones. We found strong negative correlations between fatty acid CPI and n -alkane ACL with precipitation and surface evaporation pointing at fine-scale adaptations to low moisture availability along the coastal transect. Moreover, our data indicate that the predominance of n -alkanes is reflecting the function of the wax in preventing water loss from the leaves. The hyperarid conditions and good preservation potential of both n -alkanes and fatty acids make them ideal tracers to study late Holocene climate change in the Atacama Desert.

Increased petrogenic and biospheric organic carbon burial in sub‐Antarctic fjord sediments in response to recent glacier retreat - Sonja Berg; Sandra Jivcov; Stephanie Kusch; Gerhard Kuhn; Duanne White; Gerhard Bohrmann; Martin Melles; Janet Rethemeyer (Limnology and Oceanography, 2021)
Fjords are recognized as hotspots of organic carbon (OC) burial in the coastal ocean. In fjords with glaciated catchments, glacier discharge carries large amounts of suspended matter. This sedimentary load includes OC from bedrock and terrigenous sources (modern vegetation, peat, soil deposits), which is either buried in the fjord or remineralized during export, acting as a potential source of CO 2 to the atmosphere. In sub‐Antarctic South Georgia, fjord‐terminating glaciers have been retreating during the past decades, likely as a response to changing climate conditions. We determine sources of OC in surface sediments of Cumberland Bay, South Georgia, using lipid biomarkers and the bulk 14 C isotopic composition, and quantify OC burial at present and for the time period of documented glacier retreat (between 1958 and 2017). Petrogenic OC is the dominant type of OC in proximity to the present‐day calving fronts (60.4 ± 1.4% to 73.8 ± 2.6%) and decreases to 14.0 ± 2.7% outside the fjord, indicating that petrogenic OC is effectively buried in the fjord. Beside of marine OC, terrigenous OC comprises 2.7 ± 0.5% to 7.9 ± 5.9% and is mostly derived from modern plants and Holocene peat and soil deposits that are eroded along the flanks of the fjord, rather than released by the retreating fjord glaciers. We estimate that the retreat of tidewater glaciers between 1958 and 2017 led to an increase in petrogenic carbon accumulation of 22% in Cumberland West Bay and 6.5% in Cumberland East Bay, suggesting that successive glacier retreat does not only release petrogenic OC into the fjord, but also increases the capacity of OC burial.

Depositional modes and lake-level variability at Lake Towuti, Indonesia, during the past ~29 kyr BP - Hendrik Vogel; James M. Russell; Sri Yudawati Cahyarini; Satria Bijaksana; Nigel Wattrus; Janet Rethemeyer; Martin Melles (Journal of Paleolimnology, 2015)

Large amounts of labile organic carbon in permafrost soils of northern A laska - Carsten W. Mueller; Janet Rethemeyer; Jenny Kao‐Kniffin; Sebastian Löppmann; Kenneth M. Hinkel; James G. Bockheim (Global Change Biology, 2015)
Permafrost‐affected soils of the northern circumpolar region represent 50% of the terrestrial soil organic carbon ( SOC ) reservoir and are most strongly affected by climatic change. There is growing concern that this vast SOC pool could transition from a net C sink to a source. But so far little is known on how the organic matter ( OM ) in permafrost soils will respond in a warming future, which is governed by OM composition and possible stabilization mechanisms. To investigate if and how SOC in the active layer and adjacent permafrost is protected against degradation, we employed density fractionation to separate differently stabilized SOM fractions. We studied the quantity and quality of OM in different compartments using elemental analysis, 13 C solid‐phase nuclear magnetic resonance ( 13 C ‐ NMR ) spectroscopy, and 14 C analyses. The soil samples were derived from 16 cores from drained thaw lake basins, ranging from 0 to 5500 years of age, representing a unique series of developing Arctic soils over time. The normalized SOC stocks ranged between 35.5 and 86.2 kg SOC m −3 , with the major amount of SOC located in the active layers. The SOC stock is dominated by large amounts of particulate organic matter ( POM ), whereas mineral‐associated OM especially in older soils is of minor importance on a mass basis. We show that tremendous amounts of over 25 kg OC per square meter are stored as presumably easily degradable OM rich in carbohydrates. Only about 10 kg OC per square meter is present as presumably more stable, mineral‐associated OC . Significant amounts of the easily degradable, carbohydrate‐rich OM are preserved in the yet permanently frozen soil below the permafrost table. Forced by global warming, this vast labile OM pool could soon become available for microbial degradation due to the continuous deepening of the annually thawing active layer.